Harmony Perception in Prelingually Deaf, Juvenile Cochlear Implant Users - Zimmer, Victoria; Verhey, Jesko L.; Ziese, Michael; Böckmann-Barthel, Martin (Frontiers in Neuroscience, 2019)
Prelingually deaf children listening through cochlear implants may be hampered in using music as a positive factor for development, since the hearing device degrades relevant details of the soundwave. An important parameter of music is harmony, transporting emotional as well as syntactic information. The present study addresses musical harmony in three psychoacoustic experiments in young, prelingually deaf cochlear-implant listeners and normal-hearing peers. The discrimination and preference of typical musical chords were studied, as well as cadence sequences conveying musical syntax. No difference of the groups emerged in the preferred chord types. The ability to discriminate chords depended on the hearing age of the cochlear-implant listeners and was less accurate than for the normal-hearing peers. Finally, the categorization of cadences was virtually not possible for the cochlear-implant listeners, whereas it was facile but improving with age in their normal-hearing peers. In contrast to them, the categorization of cadences was virtually impossible for the cochlear-implant listeners. This dissociation is in accordance with data found in postlingually deafened adults. Consequently, musical harmony is available to a limited degree to cochlear implant listeners, but they hardly utilize it for interpreting musical syntax.